Pedagogi sentuhan batin: Rekonstruksi kompetensi guru Sekolah Minggu melalui pendekatan afektif-kontemplatif - Tuju, Rifky Serva; Hernawan, Asep Herry; Rusman (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2026)
Sunday school teachers occupy a foundational role in the spiritual formation of children within Christian communities. However, prevailing pedagogical frameworks remain predominantly cognitive and content-transmissive, neglecting the affective and contemplative dimensions essential to holistic spiritual formation. This article proposes